Public policy implementation: concept and the main intervening factors - Silvana Menegoto Nogueira Di Giusto; Vanda Mendes Ribeiro (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2019)
This paper presents the concept of "public policies implementation" and the main factors that interfere in this phase of policy. The references came from a survey done in Scielo with the keywords "public policies implementation" and "Educational Policies", in the year 2017, in addition to research presented at meetings of Reippe. From the literature used, it can be seen that the implementation of public policies can be considered a phase of the policy in which implementing agents interact in the provision of public services foreseen in guidelines to the beneficiaries. For this literature, the implementation is not the simple rational execution of guidelines, but, fundamentally, the fruit of interactions carried out with purposes, in which they interfere a set of factors, among them: the different contexts, working conditions, patterns of interactions between the implementing agents, the discretion of these agents, their different interpretations resulting from communication processes, training and also their personal beliefs and values.